2005
DOI: 10.1128/jcm.43.5.2155-2162.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibilities of Candida Species Causing Vulvovaginitis and Epidemiology of Recurrent Cases

Abstract: There are limited data regarding the antifungal susceptibility of yeast causing vulvovaginal candidiasis, since cultures are rarely performed. Susceptibility testing was performed on vaginal yeast isolates collected from January 1998 to March 2001 from 429 patients with suspected vulvovaginal candidiasis. The charts of 84 patients with multiple positive cultures were reviewed. The 593 yeast isolates were Candida albicans (n ‫؍‬ 420), Candida glabrata (n ‫؍‬ 112), Candida parapsilosis (n ‫؍‬ 30), Candida krusei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

56
297
9
26

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(388 citation statements)
references
References 30 publications
56
297
9
26
Order By: Relevance
“…Only three isolates had dose-dependent susceptibility or resistance to fluconazole, all of these were C. glabrata present in the vaginal mucosa of HIV-1-infected patients. These data are in agreement with other studies [23][24][25] that described azole refractory vaginitis caused by non-albicans Candida, particularly by C. glabrata. 23 Non-albicans Candida infections frequently require the use of non-azole therapy, including topical therapy with boric acid, Flucytosine, or Amphotericin B.…”
Section: Discussionsupporting
confidence: 93%
“…Only three isolates had dose-dependent susceptibility or resistance to fluconazole, all of these were C. glabrata present in the vaginal mucosa of HIV-1-infected patients. These data are in agreement with other studies [23][24][25] that described azole refractory vaginitis caused by non-albicans Candida, particularly by C. glabrata. 23 Non-albicans Candida infections frequently require the use of non-azole therapy, including topical therapy with boric acid, Flucytosine, or Amphotericin B.…”
Section: Discussionsupporting
confidence: 93%
“…The recommended regimens including induction therapy at times up to two weeks followed by maintenance therapy for up to six months, which have been supported by randomized clinical trials [115], have numerous challenges. The repeated treatments may increase the likelihood of drug resistance as well as shift the spectrum of causative Candida spp [76,89,[95][96][97]. The same has been said with regards to widespread use of azole compounds especially when the diagnosis is not confirmed [14,142].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of non-albicans Candida spp in RVVC which has been shown to be more common in the developing countries is a worrying situation as C. glabrata has been shown to have high minimum inhibitory concentration (MIC) to azole, and C. krusei is intrinsically resistant to fluconazole [131,144]. Richter et al [89] reported that 67% of C. glabrata from vaginal isolates were not susceptible to azole compounds [89]. Though boric acid is very effective in their treatment its efficacy ends with cessation of treatment [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1999; Willis et al 1999;Richter et al 2005). These infections include oropharyngeal candidiasis, esophageal candidiasis, vulvovaginal candidiasis, and cutaneous candidiasis.…”
mentioning
confidence: 99%